Exogenous and Endogenous Learning Resources in the Actiotope Model of Giftedness and Its Significance for Gifted Education. (December 2017) - Ziegler, Albert; Chandler, Kimberley L.; Vialle, Wilma; Stoeger, Heidrun
Based on the Actiotope Model of Giftedness, this article introduces a learning-resource-oriented approach for gifted education. It provides a comprehensive categorization of learning resources, including five exogenous learning resources termed educational capital and five endogenous learning resources termed learning capital . Evidence from the literature is presented that supports the validity of each of the categories. Finally, 12 implications of a learning resource orientation for gifted education are discussed in relation to four areas: gifted education orientations, gifted identification, gifted education principles, and gifted learning resources management.